2019
DOI: 10.1136/annrheumdis-2018-214802
|View full text |Cite
|
Sign up to set email alerts
|

All-cause, cause-specific and age-specific standardised mortality ratios of patients with systemic lupus erythematosus in Ontario, Canada over 43 years (1971–2013)

Abstract: BackgroundSurvival in systemic lupus erythematosus (SLE) has improved substantially in the last 50 years. The aim of the present study was to assess the evolution of the all-cause, cause-specific and age-specific standardised mortality ratios (SMRs) of patients with lupus in Ontario, Canada.Patients and methodsBetween 1971 and 2013, 1732 patients were followed in the Toronto Lupus Clinic. Causes of death were retrieved from death certificates, autopsy reports, hospital records or the records of the family phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
72
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 20 publications
3
72
0
1
Order By: Relevance
“…Renal survival and mortality rates in our patients are similar to most other cohorts [ 22 ], as are the main causes of death [ 23–26 ]. In contrast, a Japanese study with 186 LN patients showed lower ESRD and mortality rates; however, more than one-third of the patients included had mesangial LN (class I and II), which is associated with a significantly better prognosis and does not require the same treatment as class III, IV or V [ 27 ].…”
Section: Discussionsupporting
confidence: 83%
“…Renal survival and mortality rates in our patients are similar to most other cohorts [ 22 ], as are the main causes of death [ 23–26 ]. In contrast, a Japanese study with 186 LN patients showed lower ESRD and mortality rates; however, more than one-third of the patients included had mesangial LN (class I and II), which is associated with a significantly better prognosis and does not require the same treatment as class III, IV or V [ 27 ].…”
Section: Discussionsupporting
confidence: 83%
“…In line with other observations, the overall SMR was found to be 1.63 (‘All incident SLE patients’) and 2.09 (‘Treated SLE patients’) in our study. While a recent study investigating a longer time period demonstrated a significant reduction of all-cause and cause-specific SMR compared with the general population from 13.5 to 2.2 [ 24 ] and early survival among SLE patients has improved substantially, epidemiological studies still show an increased mortality rate in SLE compared with the general population [ 25–27 ]. A wide range of recent studies report values of SMR for the adult SLE population between 2.4 and 3.5 in Europe and North America [ 18 , 20 ], and up to 2.58–5.25 in Asian countries [ 18 , 19 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Björnådal et al found that cardiovascular mortality remained high, especially in younger population between 1964 and 1995 [ 32 ]. Tselios et al [ 24 ] used ICD-10 codes that cover the atherosclerotic diseases (both cardiac or cerebrovascular) and found that the cause-specific SMR decreased from 8.3 in the 1980s to 3.2 in the most recent years (2010–13), with an average of 4.7. An SMR of 2.97 for coronary heart disease and stroke was reported in Sweden for the period of 1964–95 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations